Answer:
See the attachment below.
Step-by-step explanation:
Best Regards!
Answer:
(5, - 4 )
Step-by-step explanation:
Given the 2 equations
2x + 3y = - 2 → (1)
3x - y = 19 → (2)
Multiplying (2) by 3 and adding to (1) will eliminate the y- term
9x - 3y = 57 → (3)
Add (1) and (3) term by term to eliminate y
(2x + 9x) + (3y - 3y) = (- 2 + 57), that is
11x = 55 ( divide both sides by 5 )
x = 5
Substitute x = 5 into either of the 2 equations and solve for y
Substituting into (1)
2(5) + 3y = - 2
10 + 3y = - 2 ( subtract 10 from both sides )
3y = - 12 ( divide both sides by 3 )
y = - 4
Solution is (5, - 4 )
Answer:
the answer is R
Step-by-step explanation:
I just took a quiz and got it correct
W=A\L
Divide L from both sides
The L in the right cancels out
Did you ever get an answer?